Европейский раскол между элитами и гражданами - Халлер, М. (Iнститут соціології НАН України, 2009)
The process of European integration since World War II has been led almost exclusively by political elites. They are also much more proud of Europe than ordinary citizens. The split between elites and citizens turns out also when looking at referenda on the integration process in the different member states of the EU. Only in half of them the population was asked about this far-reaching process; where referenda were carried out, a much stronger endorsement of the integration among the parliamentary deputies than among the general populations could be observed. This paper explains the split between elites and citizens by proposing two general theses: First, all three power elites - political, economic and bureaucratic - have particular interests in the process of European integration; for the population at large, the benefits of integration have been much more modest than praised by the elites. Both these theses are documented in this paper by using data on the historical development of the EEC/EU, data on its institutional set-up, and on perceptions and opinions of the citizens in the different member countries. The paper concludes that the investigation of the issue of decreasing political trust and legitimacy in modern democracies in general and in the European Union in particular is an urgent task.